Roman history and culture in the historical memory of Britons (according to Nennius' "Historia Brittonum") - Малюгин О. (Київський національний університет імені Тараса Шевченка, 2012)
The article deals with representations of the inhabitants of the Celtic regions of the British Isles about Roman history and culture and their influence on the political situation at that time (VIII–IX cc.)
Римська історія та культура в історичній пам'яті бритів (за "Історії бритів" Неннія)